(3GdTGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGejf (B... (3abO SCdfj ef dG jSYfj eVGjbJg hdG jhGabfj eNGdaJg Cf oCdMb HebOeJj aj GdEYQGH ebOeI aj GdJUQja Yi fMhgG ebOeI aj GdNW aCLHJg SGFdG eJVQYG Cf jfaY HgeG (B...s
(3BNQgG (B:s
(3hHGdeVGQY fMh jQej hjZRh hjchf GdaGA hGhG fMh hYj hjchf GdYjf hGhG fMh Thi EdG eG TP fMh Gdbhi hGdghG aEf Lgd aEf aGdjGA fMh eJi EdG aGdGda hEfeG cJHh GdPj HGdjGA dbhdge (B...(3JeJ JeJs
(3HBNQgG WjGQGJ efaQOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\211s
(3cTa GdXfhf (B1\1021s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdUQas